2010
DOI: 10.1007/s11095-010-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Particle Aerosolisation and Break-up in Dry Powder Inhalers 1: Evaluation and Modelling of Venturi Effects for Agglomerated Systems

Abstract: While this study focussed on the effect of turbulence on agglomerate break-up, the small amount of impaction, which inevitably occurs in the venturi assembly, appeared to dominate agglomerate break-up in this dry powder system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…The third CFD performance measure is used to characterize the nature of the impacts during carrier particleinhaler collisions, which were previously suggested to be one of the dominant factors in inducing deaggregation of drug particles from lactose carriers in DPI devices (15,30). These CFD performance measures, as summarized in Table II, are intended to illustrate important trends in the aerosolization performance of the DPI devices rather than to provide quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third CFD performance measure is used to characterize the nature of the impacts during carrier particleinhaler collisions, which were previously suggested to be one of the dominant factors in inducing deaggregation of drug particles from lactose carriers in DPI devices (15,30). These CFD performance measures, as summarized in Table II, are intended to illustrate important trends in the aerosolization performance of the DPI devices rather than to provide quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is an established methodology for predicting the flow properties and the fate of the particulate system in the respiratory tract and inhalation devices (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). For example, Coates et al demonstrated how CFD modeling of the DPI mouthpiece geometry, dispersion grid and air inlet size (11), airflow rate (12), and capsule properties (13) could be used to investigate aerosol performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, using the ICRP 66 model for predicting deposition patterns (in patients) after drug inhalation with a metered dose inhaler (MDI) or dry powder inhaler (DPI) led to overprediction of the pulmonary dose and underprediction of the mouth-throat fraction (82). Possible explanations for the constantly overpredicted pulmonary dose might be an inhaler spray momentum (ballistic effect; high aerosol velocity produced) of MDIs (83), turbulent inhaler jet effects (84), or coarse effects (particle deagglomeration dependent on inhalation flow) of DPIs (28,85). The lung deposition of a nebulizer without a strong ballistic or coarse effect was accurately predicted (82).…”
Section: Pulmonary Drug Deposition Patternsmentioning
confidence: 99%
“…23 In general, the primary mannitol powder and agglomerated systems were characterised in terms of particle size, morphology, density, mass, and surface area. The primary particle size distribution was determined using laser diffraction (Malvern Mastersizer 2000; Malvern, Worcestershire, UK) by suspending the particles in chloroform.…”
Section: Physical Characterisation Of the Primary Mannitol Particles mentioning
confidence: 99%
“…Previous studies have utilised a combination of CFD and experimental entrainment tubes to study the break-up and aerosolisation of a model agglomerate system (containing micron-sized mannitol particles) as a function of airflow, turbulence level and impact force against the surface of an entrainment tube. 23,24 The initial study utilised a series of venturi tubes to induce turbulent flow with characteristics equivalent to commercial DPI devices whilst minimising other potential break-up mechanisms (such as wall or grid impaction), whereas the subsequent study utilised a series of impactors with different impaction angles to induce agglomerate collision upon the impact surface whilst reducing the effect of break-up in turbulent flow. Interestingly, these studies found agglomerate impaction to play a more dominant role in the aerosol performance.…”
Section: Introductionmentioning
confidence: 99%